Analisis Peningkatan Literasi Digital Siswa melalui Edukasi Interaktif Berbasis Tools Digital dan Pre-Post Test - Khairani Puspita; Nita Sari Br Sembiring; Peter Jaya Negara Simanjuntak; Nia Mardiah; Armayse Rolando Piherta (Penerbit Goodwood, 2026)
Purpose: This study aims to improve digital literacy understanding and raise awareness among Grade XII students of Sekolah Menengah Kejuruan Swasta (SMKS) Budi Agung Medan in using technology productively to support digital economic activities. Methodology: The study used a pre-test and post-test design involving 25 students through digital literacy outreach and education. The materials included digital literacy concepts, the use of tools (Canva, CapCut), and digital economic activities such as content creation and affiliate programs. Results: The average score increased from 94.0 to 98.2, with the minimum score improving from 80 to 90. The number of students achieving perfect scores rose from 18 to 21, indicating improved understanding and awareness. Conclusions: Digital literacy outreach effectively improves students’ knowledge, awareness, and responsible use of technology in the digital economy. The program also encourages students to use digital tools more critically, ethically, and productively. Limitations: This study involved only 25 students from one school, limiting the generalizability of the findings. It also focused on short-term outcomes without measuring long-term behavioral changes. Contributions: This study shows that digital literacy programs can improve students’ digital competencies and provides a useful reference for schools, educators, and policymakers in developing technology-based educational initiatives.